(3GdeYGfj GdObjbI aj EOQGc GdMbjbIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3hHYO CcKQhG ef ESJTcGdgG hCHOhG dgG CbGhjdkG deG Nai Ydjge ef MGdgG hhbY dge Pdc aj ehVYjf s
(3BNQgG (B:s
(3hGdcdGe aj gPG cKjQ LOkG hMbjbI EOQGc GdYed ddYGQa eTGgOI hdG EfcGQ Ydjg Je gPG GdcJGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1729s
Keywords: (3GdMOjK h GdeUWdMs